2 best friends received Excellence Prizes in Dual-Degree Programme (Verein Deutscher Ingenieure Award) - UMP, PNC (2018)
It was indeed a moment to cherish for these two best friends, Nor Amirah Mohamad Radzuan and Nur Syakiroh Saidin for each received the Excellence Prize for the Dual-Degree Programme (Verein Deutscher Ingenieure Award) during Universiti Malaysia Pahang (UMP) 13th Convocation Ceremony that was held on November 10 and 11, 2018.